Pelatihan Sablon dan Pembuatan Papan Bunga menciptakan Peluang Bisnis bagi Karang Taru na Sunua Tengah - Murdy, Khairi; Sofia, Nita; Sami, Yasrul (Universitas Pahlawan Tuanku Tambusai, 2025)
Nagari Sunua Tengah in Padang Pariaman Regency has excellent potential to develop youth creativity through economic empowerment programs. The high poverty level in this area is a significant concern, especially for Karang Taruna as an agent of change. Screen printing and flower board-making training were chosen to improve technical skills while opening new business opportunities. This program combines production skills with strategic entrepreneurship, such as digital marketing and business management. The methods used in this training are coaching, lectures, QA and mentoring. The training results showed increased participants’ abilities in producing high-value economic goods through screen printing t-shirts and flower boards and strengthening community collaboration. This activity supports local economic development while creating new job opportunities, aligning with the vision of community empowerment based on local potential. This training sustainably impacts the financial independence of the youth and the Nagari Sunua Tengah community.